Cultivares, qualidade de tubérculos e comercialização da batata no Brasil - Figueiredo, Priscila Gonzales [UNESP]; Tanamati, Fábio Yomei [UNESP]; Martins, Dagoberto [UNESP]; Bicudo, Silvio José [UNESP]; Curcelli, Felipe [UNESP] (My University, 2011)
Currently, the potato is the 4th largest source of food for man, being surpassed in terms of production for wheat, corn and rice. Brazil represents 1% of potatoes world production, being self-sufficient in-nature potato production, but it´s still importers of frozen potatoes, and per capita consumption is low compared to European countries. The potato stands out as the horticultural crop of greater economic importance for the country, with an output of over 3 million tons to 140 thousand hectares per year. Although the representation of culture in the country, the consumer preference for fresh washed potatoes and yellow peel and flesh, cause losses in potato production chain. This work aimed to analyze the landscape of potato cropping in Brazil in terms of varieties available and / or cultivated tuber quality and marketing.

Atualmente, a batata constitui a quarta maior fonte de alimento para o homem, superada em termos de produção pelo trigo, milho e arroz. O Brasil apresenta 1% da produção mundial de batatas, sendo autosuficiente na produção e comercialização da batata in natura, entretanto ainda é importador de batata congelada, e o consumo per capita é baixo comparado aos países europeus. A batata se destaca como a cultura olerácea de maior relevância econômica para o país, com produção de mais de 3 milhões de toneladas em 140 mil hectares ano-1. Apesar da representatividade da cultura no país, a preferência de compra por batatas in natura, lavadas, de película lisa e brilhante, e polpa amarela, acarreta prejuízos na cadeia produtiva da batata. Diante do exposto objetivou-se analisar o panorama da bataticultura no Brasil, em termos de cultivares disponíveis e cultivados, qualidade de tubérculos e sua comercialização.
Variety, quality potato tubers and marketing in Brazil
Keywords: Solanum tuberosum; Losses; Iimprovement; Solanum tuberosum; Perdas; Beneficiamento